2017
DOI: 10.1103/physics.10.64
|View full text |Cite
|
Sign up to set email alerts
|

Closing in on a Magnetic Analog of Liquid Crystals

Abstract: We report a 51 V nuclear magnetic resonance investigation of the frustrated spin-1=2 chain compound LiCuVO 4 , performed in pulsed magnetic fields and focused on high-field phases up to 56 T. For the crystal orientations H∥c and H∥b, we find a narrow field region just below the magnetic saturation where the local magnetization remains uniform and homogeneous, while its value is field dependent. This behavior is the first microscopic signature of the spin-nematic state, breaking spin-rotation symmetry without g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…as pointed out in Ref 28. and ESR might reveal excitation of bound magnon pair typical of a QN phase29 .…”
mentioning
confidence: 68%
“…as pointed out in Ref 28. and ESR might reveal excitation of bound magnon pair typical of a QN phase29 .…”
mentioning
confidence: 68%
“…There is good theoretical evidence that SN order should occur in a wide range of systems, including thin films of 3 He; cold atoms in an optical lattice; and a wide variety of quantum magnets with competing, or “frustrated,” interactions. The simplest candidate is the spin-1 system in which spin quadrupole moments of spin-1 form a quadrupolar order (2), although its observation is still elusive (3). Among other widely discussed examples are quantum spin chains (48) and square-lattice Heisenberg models (912) where ferromagnetic first-neighbor interactions ( J 1 ) compete with antiferromagnetic second-neighbor interactions ( J 2 ), in applied magnetic field.…”
mentioning
confidence: 99%
“…The first experiment was done for H c in a steady magnetic field [105], using the hybrid magnet at Tallahassee. It was concluded that the anomalous phase observed by magnetisation was essentially due to impurities, most of the system being saturated above 41.4 T, and that the nematic phase, if present, could only exist between 40.5 T < H < 41.4 T. However, very recent experiments conducted in pulsed magnetic field for H c and H b have shown that, in both orientations, there is a field range below the saturation field in which there is no transverse order and the observed field dependence of the hyperfine shift is identical to the change in the magnetic susceptibility [37,106], in agreement with the theoretical To each site correspond 6 lines due to the two isotopes 63 Cu and 65 Cu and the quadrupole coupling, which does not depend on the site. Note that the width of stability of the plateau is only 1.5 T which precludes any field sweep at constant frequency to obtain the full spectrum.…”
Section: Spin Laddersmentioning
confidence: 99%